753 Should Mini-Sternotomy Be Favoured Over Conventional Full-Sternotomy Approach in Aortic Valve Replacement. (12th October 2021) - Aljanadi, F; Moawad, N; Beattie, G; Nzewi, O; Jones, M; Ahmed, A
Abstract: Aim: In view of the increasing interest in Upper mini-sternotomy (UMS) as an alternative approach for conventional full sternotomy AVR (FS), we aimed to compare early and mid-term results between UMS and Full-sternotomy AVR. Method: This is a retrospective study of 231 patients who had aortic valve replacement via upper mini sternotomy (UMS) compared with 231 patients had their AVR via full sternotomy (FS). Baseline characteristics, operative and postoperative outcomes were compared. Patients' data are presented as median (interquartile range) or as percentages. Results: The two groups were almost comparable in terms of preoperative characteristics. Though patients with age >80 were more in UMS AVR group (11.25% vs 8.6%), this was statistically insignificant (p > 0.05). Females were significantly more in UMS AVR group (104 vs 66, p < 0.05), as well as in high BMI patients (120 vs 89, p < 0.05). There was no significant difference in 30-day mortality( 0.43%vs 2.2%, P > 0.05) between the two groups, as well as in cardiopulmonary bypass time (109 vs 103 min, p > 0.05), aortic cross-clamping time (82 vs 83 min, p > 0.05) and the duration of operation(218 vs 213, p > 0.05).Results showed no significant difference in the incidence of major and minor postoperative complications apart from FS AVR patients had a higher incidence of postoperative pneumonia ( 2.1% vs 10.4 %, p < 0.05). Conclusions: UMS AVR are more commonly used in females and high BMI patients. Our results show that UMS AVR is a safe alternative approach for aortic valve surgery revealing comparable early and midterm results to conventional FS AVR.